2019
DOI: 10.1016/j.invent.2019.01.004
|View full text |Cite
|
Sign up to set email alerts
|

A guided internet-delivered individually-tailored ACT-influenced cognitive behavioural intervention to improve psychosocial outcomes in breast cancer survivors (iNNOVBC): Study protocol

Abstract: BackgroundInternet-delivered interventions can provide remarkable opportunities in addressing breast cancer survivors' unmet support care needs, as they present an effective strategy to improve care coordination and provide access to efficacious, cost-efficient and convenient survivorship care. Nevertheless, research focusing on improving survivors' psychosocial needs using internet-based tools is scarce and its practical implementation is limited.ObjectivesTo study the acceptability, feasibility, efficacy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 93 publications
(122 reference statements)
0
37
0
3
Order By: Relevance
“…The equitable implementation of self-guided, guided, or blended approaches, possibly following a stepped care model, would facilitate psychoeducation delivery, contribute to citizens' empowerment, and ease the burden over healthcare providers, allowing them to focus on patients with severe conditions, ultimately contributing to the resilience of the healthcare system. However, only a handful of such programs were under development or ongoing in Portugal [e.g., (96)(97)(98)(99)] prior to the COVID-19 crisis, and, to the best of our knowledge, very few internet-delivered initiatives were developed/adapted to address COVID-19 specific constraints in the meantime (e.g., internet-delivered multimodal pre-habilitation program for confined cancer patients) (100), suggesting that well-known implementation barriers, namely clinicians' attitudes and lack of knowledge, training, and experience, persist (68). Such barriers are probably compromising the development, adaptation, and implementation of internet interventions during this crisis in Portugal.…”
Section: Internet Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The equitable implementation of self-guided, guided, or blended approaches, possibly following a stepped care model, would facilitate psychoeducation delivery, contribute to citizens' empowerment, and ease the burden over healthcare providers, allowing them to focus on patients with severe conditions, ultimately contributing to the resilience of the healthcare system. However, only a handful of such programs were under development or ongoing in Portugal [e.g., (96)(97)(98)(99)] prior to the COVID-19 crisis, and, to the best of our knowledge, very few internet-delivered initiatives were developed/adapted to address COVID-19 specific constraints in the meantime (e.g., internet-delivered multimodal pre-habilitation program for confined cancer patients) (100), suggesting that well-known implementation barriers, namely clinicians' attitudes and lack of knowledge, training, and experience, persist (68). Such barriers are probably compromising the development, adaptation, and implementation of internet interventions during this crisis in Portugal.…”
Section: Internet Interventionsmentioning
confidence: 99%
“…However, only a handful of such programs were under development or ongoing in Portugal [e.g., ( 96 – 99 )] prior to the COVID-19 crisis, and, to the best of our knowledge, very few internet-delivered initiatives were developed/adapted to address COVID-19 specific constraints in the meantime (e.g., internet-delivered multimodal pre-habilitation program for confined cancer patients) ( 100 ), suggesting that well-known implementation barriers, namely clinicians' attitudes and lack of knowledge, training, and experience, persist ( 68 ). Such barriers are probably compromising the development, adaptation, and implementation of internet interventions during this crisis in Portugal.…”
Section: Introductionmentioning
confidence: 99%
“…However, only a handful of such programs were under development or ongoing in Portugal [e.g., (96)(97)(98)(99)] prior to the COVID-19 crisis, and, to the best of our knowledge, very few internet-delivered initiatives were developed/adapted to address COVID-19 specific constraints in the meantime (e.g., internet-delivered multimodal pre-habilitation program for confined cancer patients) (100), suggesting that well-known implementation barriers, namely clinicians' attitudes and lack of knowledge, training, and experience, persist (68). Such barriers are probably compromising the development, adaptation, and implementation of internet interventions during this crisis in Portugal.…”
Section: Internet Interventionsmentioning
confidence: 99%
“…The pilot study reported high levels of engagement in all aspects of the intervention, as well as general improvements in weight, fruit and vegetable intake, and physical activity 30 . Two additional studies evaluated the effectiveness of technology-supported cognitive behavioral therapy in mitigating anxiety, depression 31 , and fatigue 32 amongst breast cancer survivors. In the latter of the two studies, the intervention group reported improved fatigue scores, functional impairment, psychological distress, and quality of life when compared to a control group 32 .…”
Section: Resultsmentioning
confidence: 99%